Protective role of lycopene on cisplatin-induced changes in sperm characteristics, testicular damage and oxidative stress in rats - Ateşşahin, A; Karahan, İ; Türk, G; Gür, S; Yılmaz, S; Çeribaşı, Ao (My University, 2006)
The aim of this studywas to investigate the possible protective role of lycopene on cisplatin (CP)-induced spermiotoxicity using quantitative, biochemical and histopathological approaches. Adult male Sprague–Dawley rats were randomly divided into four groups. The control group received physiological saline; animals in cisplatin group received only cisplatin; pre-treatment group received a 10-day of lycopene before administration of cisplatin while animals in post-treatment group received a 5-day of lycopene following administration of cisplatin. Cisplatin (7 mg kg?1) was intraperitoneally (i.p.) injected as a single dose and lycopene (4 mg kg?1) was administered by gavage in corn oil. Traits of reproductive organs; sperm characteristics, testicular histological findings, plasma testosterone levels and the testicular tissue oxidative status were determined. Administration of cisplatin to rats decreased sperm concentration (p<0.05) and sperm motility (p<0.001), increased total abnormal sperm rates (p<0.05) as compared with the control group. While a marked normalization was achieved only in sperm concentration with lycopene in pre-treatment group, significant normalizations were achieved in the sperm concentration, sperm motility, total abnormal sperm rates in posttreatment group. No significant differences in levels of testosterone were observed among all groups. An increase in testes malondialdehyde concentrations (p<0.05) and glutathione peroxidase activities (p<0.001) were detected while significant decreases in glutathione levels (p<0.001) in cisplatin alone group when compared to control group. While pre-treatment with lycopene restoring only malondialdehyde concentrations, its post-treatment caused normalization in both malondialdehyde and glutathione levels when compared with the cisplatin alone group. On the other hand, significant increases were determined in GSH-Px activities in all experimental groups when compared with the control group. Although the mechansim is not clear, the results from this experimental study suggest that the lycopene have a possible protective effect against cisplatin-induced spermiotoxicity, effect of giving lycopene after cisplatin being superior to the giving it before cisplatin.
Sıçanlarda sispilatinin neden olduğu sperm özellikleri, testiküler hasar ve oksidatif stres üzerine likopenin koruyucu rolü
Makale - Yabancı Dilde Makale
Keywords: Cisplatin Lycopene Sperm characteristics Testosterone Lipid peroxidation Histopathology Rat